Pentavalent vaccine and vaccination coverage in children aged less than one in Colombia 2000-2003 (2006)
Objective: Determining the impact of including pentavalent vaccine in third-dose immunisation coverage for children aged less than 1 (2002 and 2003) by geographic cluster. Materials and methods: This was an ecologic study using department, province, municipality and capital city as analysis units. It compared third-dose coverage, desertion index, number of places having more than 80 % immunisation coverage and the number of children being immunised before and after vaccination was introduced. Having more than 80 % immunisation coverage was compared to the number of children or places having unsatisfied basic needs, the presence of armed conflict or municipal category. Results: Immunisation coverage increased from 23 % to 26 %, mainly for Hib3. Desertion index was 9,3-31,7 % in 2000 and 0,3 % in 2003. The number of municipalities having more than 80 % immunisation coverage increased from 265 in 2000 to 627 in 2003. 462 000-584 000 third-doses were applied in 2000 and 805 000-813 000 in 2003. More municipalities having more than 80 % coverage had high unsatisfied basic needs, low socioeconomic income or conflict. Conclusions: The introduction of the vaccine affected immunisation coverage. Financing should be sought for the vaccine to ensure its continuity and to implement studies for new vaccines or introducing combination vaccines.